Prevalence Of Urinary Tract Infection Among Primary School Children In Maiduguri, Borno State, Nigeria - Isa, MA; Ismail, HY; Allamin, IA; Shettima, A; Mustapha, A (International Journal of Environment, 2013)
The prevalence of urinary tract infection (UTI) among children attending primary schools in Maiduguri was investigated in this study. The study was carried out between January and April 2011 among apparently healthy pupils. One hundred and twenty (120) clean-catch urine samples were obtained from the pupils using standard procedures. Microbial culture on Cystein Lactose Electrolyte Deficient (CLED) ager and subsequent Biochemical tests revealed 31.7% of the samples with significant bacterial growth (≥ 105 CFU/ml). Among the identified organisms Escherichia coli were more prevalent (8.3%) among the identified organisms, while Proteus and Klebsiella species were less prevalent (1.6% each). Other species that were identified include Staphylococcus aureus (6.7%), Streptococcus faecalis (4.2%), Staphylococcus saprophyticus (3.3%) and Corynebacterium species (5.8%). Urinalysis to detect haematuria as presumptive test for UTI was insignificant (P > 0.05). Only 2 (out of 5) samples showed bacteriuria in culture plates. Association of gender, previous history of UTI, bedwetting and presence of blood in urine related prevalence were tested, only sex was strongly associated with UTI (p < 0.05). The incidence of UTI in females (19.5%) was higher than males (12.5%). Therefore, government needs to increase efforts toward creating awareness among the people, for effective treatment, control and prevention of the disease. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 9-15 DOI: http://dx.doi.org/10.3126/ije.v2i1.9203